Microbiota profiling reveals alteration of gut microbial neurotransmitters in a mouse model of autism-associated 16p11.2 microduplication - Fu, Zhang; Yang, Xiuyan; Jiang, Youheng; Mao, Xinliang; Liu, Hualin; Yang, Yanming; Chen, Jia; Chen, Zhumei; Li, Huiliang; Zhang, Xue-Song; Mao, Xinjun; Li, Ningning; et al. (Frontiers in Microbiology, 2024)
The gut-brain axis is evident in modulating neuropsychiatric diseases including autism spectrum disorder (ASD). Chromosomal 16p11.2 microduplication (dp) is among the most prevalent genetic copy number variations (CNV) linked with ASD. However, the implications of gut microbiota status underlying the development of ASD-like impairments induced by 16p11.2dp remains unclear. To address this, we initially investigated a mouse model of 16p11.2dp/+, which exhibits social novelty deficit and repetitive behavior. Subsequently, we conducted a comparative analysis of the gut microbial community and metabolomic profiles between 16p11.2dp/+ and their wild-type counterparts using 16S rRNA sequencing and liquid chromatography-mass spectrometry (LC/MS). Our microbiota analysis revealed structural dysbiosis in 16p11.2dp/+ mice, characterized by reduced biodiversity and alterations in species abundance, as indicated by α/-diversity analysis. Specifically, we observed reduced relative abundances of Faecalibaculum and Romboutsia, accompanied by an increase in Turicibacter and Prevotellaceae UCG_001 in 16p11.2dp/+ group. Metabolomic analysis identified 19 significantly altered metabolites and unveiled enriched amino acid metabolism pathways. Notably, a disruption in the predominantly histamine-centered neurotransmitter network was observed in 16p11.2dp/+ mice. Collectively, our findings delineate potential alterations and correlations among the gut microbiota and microbial neurotransmitters in 16p11.2dp/+ mice, providing new insights into the pathogenesis of and treatment for 16p11.2 CNV-associated ASD.